The role of adjuvant treatment in early‐stage oral cavity squamous cell carcinoma: An international collaborative study - Fridman, Eran; Na'ara, Shorook; Agarwal, Jaiprakash; Amit, Moran; Bachar, Gideon; Villaret, Andrea Bolzoni; Brandao, Jose; Cernea, Claudio R.; Chaturvedi, Pankaj; Clark, Jonathan; Ebrahimi, Ardalan; Fliss, Dan M.; et al. (Cancer, 2018)
BACKGROUND Up to half of patients with oral cavity squamous cell carcinoma (OCSCC) have stage I to II disease. When adequate resection is attained, no further treatment is needed; however, re‐resection or radiotherapy may be indicated for patients with positive or close margins. This multicenter study evaluated the outcomes and role of adjuvant treatment in patients with stage I to II OCSCC. METHODS Overall survival (OS), disease‐specific survival, local‐free survival, and disease‐free survival rates were calculated with Kaplan‐Meier analysis. RESULTS Of 1257 patients with T1‐2N0M0 disease, 33 (2.6%) had positive margins, and 205 (16.3%) had close margins. The 5‐year OS rate was 80% for patients with clear margins, 52% for patients with close margins, and 63% for patients with positive margins (P < .0001). In a multivariate analysis, age, depth of invasion, and margins were independent predictors of outcome. Close margins were associated with a >2‐fold increase in the risk of recurrence (P < .0001). The multivariate analysis revealed that adjuvant treatment significantly improved the outcomes of patients with close/positive margins (P = .002 to .03). CONCLUSIONS Patients with stage I to II OCSCC and positive/close margins have poor long‐term outcomes. For this population, adjuvant treatment may be associated with improved survival. Cancer 2018;124:2948‐55. © 2018 American Cancer Society. Patients with stage I to II oral cavity squamous cell carcinoma and positive/close margins have poor long‐term outcomes. For this population, adjuvant treatment is associated with improved survival.